PHOTODYNAMIC THERAPY WITH PHOTOSENSITIZER PHOTOLON FOR BASAL CELL CARCINOMA - D. A. Tzerkovsky; A. N. Mazurenko; N. A. Petrovskaya; T. P. Artemyeva (Biomedical Photonics, 2017)
The short-term and long-term outcomes of treatment in 130 patients with basal cell carcinoma (T1N0M0, I stage) using photodynamic therapy with photosensitizer photolon based on chlorine e6 are represented in the article. The session of photodynamic therapy was performed 2.5-3 h after intravenous injection of photolon at dose of 2-2.5 mg/kg using semiconductor laser (λ=660±5 nm, laser power density — from 0.1 to 0.52 W/cm2, light dose — from 50 to 300 J/cm2). Complete regression of primary and recurrent carcinomas was observed in 90.9% and 88.9% of patients, respectively. For follow-up period of 3 to 76 months the local recurrence of the tumor was in detected in 6.9% of cases. Patients, who followed the light regimen for 2–3 days after photolon administration avoiding direct sun light exposure, had no manifestation of phototoxicity. Ten patients who failed to follow the light regimen had mild hyperemia, itching and burning in the exposed skin area selflimiting in several hours. Cosmetic results of photodynamic therapy with photolon are superior to those for traditional treatment methods for this disease.